INVESTIGATION OF THE MICROBIOLOGICAL PROPERTIES OF FRESH VEGETABLES FROM RURAL MARKETS IN ENUGU STATE, NIGERIA - Ikwuegbu, Esther C. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
Several disparate studies have identified vegetables as an essential part of plants that contributes immensely to health and wellbeing. Importantly, vegetables represent a ubiquitous source of nutrients and dietary fiber required for proper health maintenance. However, growing insinuation suggests that vegetable consumption is associated with several pathogenic organisms that are of public health concern. The present study was conducted to identify and isolate the bacterial composition of fluted pumpkin, bitter leaf, and scent leaf frequently sold at various markets in Enugu State. The bacteria were evaluated with the standard microbiological procedure using the serial dilution method. The result showed that the samples collected from different vendors contained various microbial loads. It was indicated that the bitter leaf had a higher bacteria load, while the pumpkin leaf held a moderate load of bacteria, and the scent leaf recorded the lowest plate count. Most importantly, Pseudomonas species, Bacillus, Erwinia spp, and Streptococcus were the primary bacteria isolated. Accordingly, the paper concluded that most vegetables obtained from the rural markets are likely to be loaded with numerous bacteria beyond the acceptable recommendations of the world health organization. The study has implications for health maintenance and wellbeing.